Efektivitas Program FRANCH Terhadap Perubahan Power Atlet Perempuan Bola Voli Kelas Khusus Olahraga DISPORA Kota Semarang - Akbari, Cakra Rizki; Ali, Mohammad Arif; Sugiarto, Sugiarto (Universitas Negeri Surabaya, 2023)
ABSTRACT Background: Jumping is one of the most important components in the game of volleyball, jumping helps athletes to play volleyball well. The purpose of this study was to determine the effect of hurdle hops tranning on jumping skills in famale volleyball athletes in the Kelas Khusus Olahraga Semarang City. Methods : This type of research is an experiment with a protest-posttest design. The population in this study were athletes in the women’s volleyball club for the Kelas Khusus Olahraga with a total of 17 athletes. The sample data collection tecnique was purposive sampling, the number of samples used was 17 famale athletes. The instrument used in the research is a vertikal jump test. Results: The analysis obtained is in the form of quantitative descriptive statistical data with the frequency obtained divided by the total sample multiplied by 100%. The results showed that the components of the physical condition of women’s volleyball players in the Kelas Khusus Olahraga in the moderate category. Conclusions: It can be concluded that the athlete’s physical condition is still in the sufficient category and the dominant physical condition component of the player is power. Keywords: vertikal jump; hurdle hops